The need to rethink African "Ideas of Christ" in the search for human flouring in post‐Covid‐19 era. Issue 3 (27th April 2021) - Kaunda, Chammah J.
Abstract: This article argues that if the African church is to make a meaningful contribution to human survival, livelihood, and dignity in post‐Covid‐19, it must reclaim and reconstitute the Christ of the marginalized and excluded who joins them in their suffering, struggles, and hopes for a liberated and emancipated post‐Covid‐19 Africa. This requires a passionate commitment to rethinking the idea of Christ as a critical resource to mobilize the masses for transformation and bettering their social contexts. The article concludes that the apparent contradiction between Christocapitalist Christian faith and the historical struggles of the masses reveals the underlying contradiction within most churches' conceptions of Christ.